HISTORICAL KNOWLEDGE IN CROSS-CULTURAL SPACE OF THE NORTH CAUCASUS XIX - EARLY XX CENTURY: ORAL AND WRITTEN PRACTICES OF CONSTRUCTING THE PAST. PART 1 - M. E. Kolesnikova; S. I. Malovichko (Гуманитарные и юридические исследования)
A series of articles examines the problem of functioning of different forms of historical knowledge in cross-cultural space of the North Caucasus in 19 - early 20th century. The first paper focuses on functioning of local oral tradition, an Islamic historical writing and the European model of history introduced by the Russian Empire which in the form of popular history (nonacademical) was positioned by the Russian teachers, military and officials. The conclusion is drawn that the European model of historical knowledge began to displace other practices of constructing the past from the region as "erroneous" and "unscientific"ones .